Desenvolvimento de um veículo aéreo não-tripulado de segurança e monitoramento - Pina, Ricardo Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In this work, is proposed a methodology for conceptual subsonic class 2 VANT’s project, basing on existing methodologies about manned and subsonic aircrafts, performing necessary considerations and adaptations for a better accommodation for the new created method and discarding unnecessary steps that are not applicable on this field. Finally, a conceptual testing project was developed for military application such as monitoring and security in order to validate the proposed method, seeking to maximize important performance indices for the category, such as endurance and fuel economy, in addition to minimize construct complexity and maintenance.

Neste trabalho propõe-se uma metodologia para o projeto conceitual de VANTs subsônicos classe 2, baseando-se em metodologias já existentes e consolidadas para aeronaves tripuladas e subsônicas, realizando adaptações e considerações necessárias para a melhor acomodação do método criado e descartando etapas desnecessárias que não se aplicam à este nicho. Afim de testar e validar a metodologia proposta, desenvolveu-se o projeto conceitual de um VANT para aplicação militar de segurança e monitoramento, buscando maximizar índices de desempenho importantes para a categoria, como autonomia e economia de combustível, além de minimizar a complexidade construtiva e de manutenção.
Development of an unmanned aerial vehicle for safety and monitoring
Keywords: Drone; Projetos; Aeronáutica militar; Engenharia aeroespacial